Restenosis risk factor and the primary patency rate of arteriovenous fistula after initial percutaneous transluminal angioplasty: a retrospective cohort study - Utari, Siti Ayu Meisa; Tua, Ivan Joalsen Mangara; Christian, David H; Caesario, Michael (Indonesian Vascular Access Association (IVAA), 2025)
Background: Arteriovenous fistula (AVF) is the optimal vascular access for patients because of its prolonged patency and limited problems. Nevertheless, maintenance is sometimes obstructed by stenosis. This study aimed to determine the factors associated with restenosis and primary patency rate in 12 months after Percutaneous Transluminal Angioplasty (PTA). Method: A retrospective study of patients who underwent initial PTA between January 2018 and October 2023. The clinical variables, laboratory indicators, and surgical data were observed in this study. The restenosis factors were analyzed by univariate analysis, Cox - Regression test, and Hosmer-Lemeshow test. The Receiver Operating Characteristic (ROC) Analysis identified the cut-off Platelet Count (PC). The primary patency of AVF with restenosis risk was evaluated using the Kaplan-Meier analysis and log-rank test. Result: A total of 54 patients were included. The Cox proportional hazard model revealed PC (p=0.004) was a risk factor for AVF restenosis. The Hosmer-Lemeshow test (χ2 = 11.130, p = 0.194) indicates our logistic regression model fits the data. Analysis of ROC identified a cut-off value of PC ≥ 210.5 x 109/L (sensitivity 85.7 %, specificity 46.2%). Primary patency rates of AVF with PC ≥ 210.5 x 109/L at 6 and 12 months (64.1% and 35.8%) were lower than those with PC< 210.5 x 10 9 /L (80.0%, 66.6%). Conclusion: Balloon type (Drug Coated Balloon and Plain Balloon), predilating balloon, balloon diameter, and inflammatory markers showed no association with restenosis in 12 months after PTA. Platelet Count is statistically significant associated with AVF restenosis, which can predict the primary patency of AVF after initial PTA. It assists physicians in establishing the follow-up schedule and appropriate intervention to prevent HD vascular access failure within 12 months post-PTA.